DESIGN OF DECY-13 CYCLOTRON DAQ SYSTEM - Ika Priyanti; Adi Abimanyu; Dr. Muhtadan; Saminto, ST (Jurnal Forum Nuklir, 2019)
PSTA BATAN (Center of Science and Accelerator Technology) has been developed the 13 MeV cyclotron named DECY-13 for producing radioisotope. That cyclotron has five subsystems and hasn’t established by communication standard protocol yet. In order to make cyclotron communicate effectively, this paper presented the design of data acquisition with OPC (OLE for Process Control) based standard protocol and it has established in DECY-13’s Instrumentation and Control System by case study method. We used Modbus TCP/IP architecture to make all of HMI from five subsystems building communication with each other to Server Computer (OPC Server). OPC Server and OPC Client has configured by NI OPC Server and NI LabVIEW. Data acquisition has monitored by LabVIEW. Configuration of the system for 13 MeV cyclotron and performance test result showed in RMSE value from Reflected Drive Amp Power is  13,94 %, Magnetic Field is 11,2 % ; Forward Final Amp Power is 5,24 % ; Forward Drive Amp Power is 1,98 % ; MPS current is 1,87 % ; Beam Current and A2 Sensor are 1,85 % ; B2 Sensor is 1,77 % ; Bias Current is 1,71%. Based on monitoring and test result, the design of DAQ system has succeeded and established  the communication from several different data types from subsystems with OPC protocol standard